10 KARAKTER SEMAR SEBAGAI MODEL PRIBADI KONSELOR - Gumilang, Galang Surya; Krisphianti, Yuanita Dwi (Nusantara of Research : Jurnal Hasil-hasil Penelitian Universitas Nusantara PGRI Kediri, 2016)
ABSTRACT This study aims to determine: (1) the character of the artifacts in the text Semar Semar, (2) private counselors drawn from the text Semar. Used a qualitative approach with Gadamerian hermeneutic method. Hermeneutic Gadamerian is a kind of hermeneutic research objective (Objectivist hermeneutics). Source data from this study are primary and secondary. The primary data comes from the book What and Who Semar Semar bouquet Sri Mulyono and the Inner Javanese Tuti Sumukti bouquet. Secondary data comes from interviews with Ki Purbo langsug Asmoro, S.Kar, Hum. The results showed that the character of Semar that can diadikan model for personal counselor, namely character (1) counsel, (2) encouragement, (3) prevention, (4) the waiter, (5) friendly, (6) wise, (7) honest (8) concerned. Key words: Semar character, private counselor